1974
DOI: 10.1055/s-0028-1093878
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypothyroidism on Serum Immunoreactive Insulin, Free Fatty Acids and Blood Sugar in the Dog as Tested for Oral Glucose Tolerance - Corrective Effects of Thyroxine Therapy

Abstract: The effect of T therapy (T 0.5 and T 10) on BS, serum IRI and FFA levels of thyroidectomized dogs during an OGTT was studied.Either T dose failed to res tore the BS profiles in these animals: T 10 corrected the delayed onset of hyperglycemia after glucose load but it definitely raised the BS baseline; T 0.5 also enhanced this baseline and, also, reduced the magnitude of hyperglycemia.Both T doses reduced the overnormal serum IRI levels observed in the thyroidectomized dogs both in the post-absorptive condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

1974
1974
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
2
4
0
1
Order By: Relevance
“…In most other studies, the concentration of insulin in hypothyroidism is reported to be normal (28) or decreased (29,30), which is similar to our result. Insulin sensitivity in hypothyroid patients has been found to be normal (31) or decreased (32)(33)(34).…”
Section: Discussionsupporting
confidence: 83%
“…In most other studies, the concentration of insulin in hypothyroidism is reported to be normal (28) or decreased (29,30), which is similar to our result. Insulin sensitivity in hypothyroid patients has been found to be normal (31) or decreased (32)(33)(34).…”
Section: Discussionsupporting
confidence: 83%
“…In most other studies, the concentration of insulin in hypothyroidism is reported to be normal 23 or decreased, 24,25 which is similar to our result. In hypothyroidism, glucose homeostasis is affected due to reduced intestinal glucose absorption, hepatic gluconeogenesis and glycogenolysis and peripheral tissue glucose disposal.…”
supporting
confidence: 83%
“…61,62 The reason for the association is not entirely clear, but an increase in plasma free fatty acids and alterations in adipocytokines and inflammatory cytokines have been proposed as possible mediators. Although these factors were not evaluated in the present study, free fatty acids are reportedly unchanged or decreased in hypothyroid dogs 5,7 ; therefore, their role in hypothyroid-mediated insulin resistance is unclear.…”
Section: Discussionmentioning
confidence: 71%
“…[4][5][6][7] Low S I and impaired glucose use associated with hypothyroidism have been identified in other animal species as well. 8,9 Whether the glucose intolerance in hypothyroidism is the direct result of thyroid hormone deficiency or whether hormones with counter-regulatory effects on insulin mediate the development of insulin resistance is unclear.…”
Section: Air Gmentioning
confidence: 96%